Empirical Studies on Phonics in Mainland China: A Systematic Review - Minjie, Chen; Soo, Ruey Shing; Lun, Wong Wei; Norhayati, Yusoff; Ping, Chuah Kee; Mohamad Syafiq, Ya Shak (2022)
Phonics is required by National Curriculum for Compulsory Education in 2011. Numerous studies were conducted on phonics and its instruction since then. To understand the research trend and to locate research gaps, a systematic review study was needed. This review was conducted based on the initial searches of China National Knowledge Infrastructure, the most popular academic platform. Following PICO tool, altogether 42 master theses are included. The findings indicate that in recent ten years, empirical studies focus on the application of phonics in EFL settings from pre-school year to high school period. Most studies were on primary school years (N=27). The findings also indicate that phonics instruction can greatly enhance EFL students’ words recognition ability, spelling ability, phonemic awareness, learning motivation as well as overall language proficiency. Based on the analysis, all the included studies has theoretical support and altogether ten different theories are utilized to support those empirical studies, although some of the studies experimental design is not strong enough. However, the findings implies no studies have been conducted on EFL teachers and preservice EFL teachers knowledge base to implement phonics, implying further investigation in this domain.